RANCANG BANGUN APLIKASI PENCATATAN LAYANAN UMKM DENGAN FITUR TRACKING TEKNISI MENGGUNAKAN GEO-LOCATION BERBASIS ANDROID (STUDI KASUS: CV. DWIRA JAYA TEKNIK) - Aditya Daffa Syahputra Aditya; Intan Purnamasari Intan; Carudin Carudin (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
CV. Dwira Jaya Teknik, an AC service MSME in Bekasi City, faces challenges regarding technician location tracking and manual operational record-keeping. This research aims to develop an Android application named "Dwira Service Manager" featuring real-time tracking with a multi-role approach. Developed through the Prototype method across four iterations, the system utilizes Kotlin with Jetpack Compose, Firebase, Cloudinary, and the Google Maps API combined with the Haversine Formula for route calculation. Evaluation was conducted using black-box testing for functional aspects and the System Usability Scale (SUS) involving three actual users. The results indicate that all functional scenarios were fully met, and the SUS evaluation yielded an average score of 75.83 with an "excellent" adjective rating ("acceptable" category), proving that the application is well-accepted and ready to optimize the company's operations.